2018
DOI: 10.1007/jhep09(2018)003
|View full text |Cite
|
Sign up to set email alerts
|

Novel 3d bosonic dualities from bosonization and holography

Abstract: We use 3d bosonization dualities to derive new non-supersymmetric dualities between bosonic quiver theories in 2 + 1 dimensions. It is shown that such dualities are a natural non-Abelian generalization of the bosonic particle-vortex duality. A special case of such dualities is applicable to Chern-Simons theories living on interfaces in 3 + 1 dimensional SU (N ) Yang-Mills theory across which the theta angle jumps. We also analyze such interfaces in a holographic construction which provides further evidence for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 22 publications
(48 citation statements)
references
References 52 publications
(135 reference statements)
4
44
0
Order By: Relevance
“…As a reminder, this duality also lives in 2 + 1-dimensions and conjectures a free Dirac fermion is dual to a U (1) × U (1) Chern-Simons matter theory, which we refer to as "QED 3 ". The generalization is a straightforward extension of previous work [11], where it was shown that the bosonic twonode quiver duality can be viewed as a generalization of the bosonic particle-vortex duality.…”
Section: B Generalized Fermion Particle-vortex Dualitymentioning
confidence: 72%
See 3 more Smart Citations
“…As a reminder, this duality also lives in 2 + 1-dimensions and conjectures a free Dirac fermion is dual to a U (1) × U (1) Chern-Simons matter theory, which we refer to as "QED 3 ". The generalization is a straightforward extension of previous work [11], where it was shown that the bosonic twonode quiver duality can be viewed as a generalization of the bosonic particle-vortex duality.…”
Section: B Generalized Fermion Particle-vortex Dualitymentioning
confidence: 72%
“…It has been shown in Refs. [11,12] that we can use two-node quivers to create generalizations of the bosonic particle-vortex duality. In this section we construct the fermionic equivalent.…”
Section: Two-node Fermionic Quiversmentioning
confidence: 99%
See 2 more Smart Citations
“…Perhaps not by coincidence, we have explicitly broken the same U (1) global symmetry in the construction of the SU (N ) Yang-Mills n-node quivers [29]. Specifically, we introduced a det (Y i,i+1 ) terms and appropriate monopole term on the U side to eliminate the U (1) n−1 symmetry.…”
Section: Double-saturated Flavor Boundmentioning
confidence: 99%